Constrained Gravity Inversion With Adaptive Inversion Grid Refinement in Spherical Coordinates and Its Application to Mantle Structure Beneath Tibetan Plateau. Issue 5 (19th May 2022) - Zhong, Yiyuan; Ren, Zhengyong; Tang, Jingtian; Lin, Yufeng; Chen, Bo; Deng, Yangfan; Jiang, Yingde
Abstract: We develop a novel gravity inversion algorithm in spherical coordinates based on adaptive inversion mesh refinement and multiphysical parameter constraints. The inversion mesh is discretized into tesseroids (spherical prisms) to take the curvature of the Earth into account. To reduce the number of unknowns and computational cost, the inversion mesh is adaptively refined according to the spatial variation of parameters at each iteration. Wavelet compression is used to further reduce the computational requirement. Besides, to alleviate the nonuniqueness of inversion, the algorithm is capable of incorporating a priori models from other geophysical methods via cross‐gradient coupling and/or direct parameter coupling. For cross‐gradient coupling, the vector product of spatial gradients of two model parameters is included in the objective function. For direct parameter coupling, an a priori model is converted to a density model using the relation between two physical properties, which is then used as the initial and reference model in the inversion. A synthetic example is presented to demonstrate the effectiveness of our inversion method. Finally, we invert the gravity data over the Tibetan Plateau to obtain the density variations in the upper mantle, with a global S wave tomographic model used as a constraint. The inversion model shows that the mantle lithosphere beneath the Himalayan collision zone varies from west to east. Low‐density anomalies are observed beneath the southern and the northern Tibetan Plateau, which are consistent with published low‐velocity anomalies and magmatism distributions, possibly indicating two asthenospheric upwellings. Plain Language Summary: Earth's gravity, following Newton's law of universal gravitation, is sensitive to density variation inside the Earth, and hence can be used to study lithospheric structures. Modern satellite technology provides a global coverage of gravity measurements, which makes gravity an efficient tool to probe the Earth. Inversion is a numerical technique to estimate physical properties in the subsurface from observed data. The computational burden for inversion usually increases dramatically with the size of a study region. In addition, inversion results suffer from strong ambiguity because of limited distribution of observation points and inevitable errors. We present a gravity inversion method to obtain density distributions in the lithosphere. The study region is first divided into small cells. The number of cells is adaptively adjusted in different areas to reduce the computational cost. Furthermore, the inversion method can exploit existing models of other physical properties to improve the result. This method is tested on a synthetic model and applied to real gravity data over the Tibetan Plateau, where how the Indian lithosphere has underthrusted is contentious. Low‐density anomalies identified in our density model might reflect asthenospheric upwellings and tearing of the Indian mantle lithosphere. Key Points: Adaptive refinement of inversion grid is used in gravity inversion to reduce the unknowns Multiphysical properties (e.g., velocity) are incorporated as constraints to improve the resolution of inversion results Inversion of gravity data over the Tibetan Plateau indicates possible asthenosphere upwellings and a fragmented Indian lithosphere